National Psoriasis Foundation Priorities for Patient-Centered Research: Proceedings from the 2016 Conference. Issue 3 (June 2017) - Afifi, Ladan; Shankle, Lindsey; Armstrong, April W.; Boas, Marc; Bridges, Alisha; Chiguil, Vivian; Frank, Doris; Duffin, Kristina Callis; Fielding, Eric; Fleischmann, Roy; Gelfand, Joel M.; Kiselica, Matthew; et al.
The National Psoriasis Foundation (NPF) is developing an agenda for patient-centered research to help patients and their caregivers make more informed health care decisions by engaging psoriasis patients in prioritizing comparative effectiveness research (CER) topics. The NPF has created a novel patient-centered research platform known as Citizen Pscientist (CP), allowing patients with psoriasis and psoriatic arthritis to register and contribute their health data. The CP Governance Council administered an online 23-question CER survey to the CP community and held a structured meeting on December 3, 2016, with patients and researchers to review CER survey results and discuss patient-centered research priorities. Of the 2, 945 patients surveyed, 792 patients responded. Three CER topics were deemed to be of high priority for the research agenda: 1) Treat-to-target therapy for psoriasis, 2) Psoriatic arthritis screening questionnaires for early detection and treatment of psoriatic arthritis, and 3) Comparative effectiveness of home-based phototherapy for psoriasis.